Laboratory-modified powder diffraction specimen holder for filter paper - Rowles, Matthew (Wiley-Blackwell, 2020)
A simple modification to an existing powder diffraction specimen holder is given to allow for the presentation of filter papers for analysis. A mild steel annulus holds the filter paper in place using magnets added to the rear of the specimen holder.